MORPHOLOGICAL ASSESSMENT AND GRADING OF HIP OSTEO ARTHRITIS USING DIFFERENT DIAGNOSTIC MODALITIES IN DOGS (Applied Biological Research, 2026)
Osteoarthritis is a degenerative disease of synovial joints. Hip is the most often afflicted joint in dogs, which makes them reluctant to walk and engage in daily activities. The present study was aimed to assess the morphological changes in osteoarthritic hip joint using radiography and computed tomography. The study was conducted on 30 dogs divided into 3 groups. Group I and II comprised of 6 young (3-5 months) and 6 adult (> 12 months age) indigenous non-lame dogs, respectively, as control. The group III comprised of 18 clinical cases of dog with hip osteoarthritis. Highest distribution of hip osteoarthritis was recorded in Labrador breed of dogs with male dogs being more frequently affected (83.33%) than females. Group II exhibited a significantly reduced joint space (0.09 ± 0.01) as compared to group I (0.19 ± 0.02). Radiographic observation of group III showed coxofemoral luxation and alterations in normal architecture of femoral head, trochanter and acetabulum due to osteophytes formation. Radiographic scoring and categorization of hip osteoarthritis revealed maximum cases (12) of severe osteoarthritis. Computed tomography scan revealed specific lesions of bony changes including presence of minor osteophytes and variation in bone density (Hounsfield unit) in osteoarthritic hip joints compared to normal joints.
Keywords: Computed tomography, diagnostic modalities, dog, hip joint, osteoarthritis